(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تكمن أهمية القيادة الإدارية باعتبارها ضرورة اجتماعية و إدارية, وهي تشكل مردوداً كلياً للعملية الإدارية, إذ لا يمكن توقع نجاح أي عمل إداري بدونها, بل إن القيادة الإدارية الناجحة هي المصدر لنجاح الشركة أو المؤسسة، وتتجلى أهمية القيادات الإدارية بالأدوار التي تمارسها هذه القيادات في الشركات القائمة عليها, مستخدمة أدوات النجاح المناسبة, والقائد الإداري المتمتع بالكفاءة والقدرة والمعرفة والسمات الشخصية والقيادية, هو المؤهل لممارسة أدواره الأساسية في القيادة, مستخدماً أدوات النجاح المتاحة بفعالية , هذه الأدوار الكفيلة بالوصول إلى تحقيق الخطط و الأهداف المبتغاة, لذلك عمدنا إلى إعداد هذا البحث الهادف إلى توضيح أهمية أدوار و أدوات نجاح القائد الإداري لمشروعاتنا, ومدى تفهمه و ممارسته لها, والمعوقات التي تواجهه وتحول دون تفعيله لبعض هذه الأدوار, وتبيان ماهية و أهمية و كفاية الأدوات المتاح استخدامها من قبل القادة الإداريين, وقد دُعمت هذه الدراسة ببحث ميداني, طبق على بعض الشركات الصناعية في سوريا بالقطاعين العام والخاص, تم التوصل من خلاله إلى الاستنتاجات والتوصيات المبينة. The importance of the administrative leadership comes from its being a social and administrative necessity that forms total output of the administrative process, because we cannot expect any administrative performance to succeed without it. A successful administrative leadership is the source of a company’s or institution success. The importance of administrative leaderships manifests through the roles these leaderships play in their companies using the suitable success tools. An efficient, powerful, expert leader with personal leadership characters is the only one qualified to fulfill the basic roles of leadership, using available success tools effectively. These roles are able to achieve plans and reach desired goals. For these reasons this study was prepared to clarify the roles and tools of the administrative leader and his understanding and using of such roles and tools. This study also explains hindrances faced that prevents a leader from activating some of these roles and describes the nature, importance, and efficiency of available tools to be used by administrative leaders. This study is supported with a field study, implemented on some industrial companies in Syria including both public and private sectors, and gives some results and recommendations.